Smart parking in fast-growing cities Challenges and Solutions - Winter, Stephan; GOEL, SALIL (TU Wien Academic Press, 2021)
"Parking in cities is a challenge everywhere, but to a greater extent for the cities in low- and middle-income countries: Cities that are experiencing rapid urbanization and increasing motorization, where free on-street parking meets haphazard parking behaviour, and where investment capacity for parking infrastructure is limited. This book is a resource book for those managing the urban parking challenges especially in low- and middle-income countries. This open-access book should immediately help city authorities, engineering firms, and academia world-wide to develop data-driven solutions - solutions of a smart city - for their specific context. This perspective is reflected in the approach of the book. The first part lays out the context of geospatial technologies for urban mobility in smart cities. The second focuses on parking information and management using these technologies, with an emphasis on low and middle-income countries. The book has grown out of a project funded by the Indian Government, Advanced Parking Information and Management for Indian Traffic, a collaboration between IIT Kanpur and the University of Melbourne. "